Acompañamiento de la familia en la enseñanza remota y la socialización en niños del programa no escolarizado de Educación Inicial Corazoncito, San Juan 2021 - Pinedo Torres, Estefany Elena (2024)
The primary purpose of this study was to establish the connection between the support provided by families during remote learning and the socialization process in the children participating in the non-formal early education program "Corazoncito" in San Juan during the year 2021. To achieve this, a quantitative, relational approach was adopted, and a non-experimental, field-based, correlational, and cross-sectional research design was employed. The study population consisted of all boys and girls, along with their respective parents, and a census sample of 42 participants was determined. Survey and observation techniques were used for data collection, utilizing a questionnaire and an observation guide. These instruments were validated through expert judgment to ensure their reliability and relevance. The study's results supported the null hypothesis, implying that there is no substantial relationship between family involvement in remote learning and the socialization process of the children who are part of the "Corazoncito" program in San Juan during the year 2021. This is confirmed through the Spearman's Rho score, which was -0.022, indicating a low-level correlation with no significant statistical significance.